Pengaruh Konsumsi Berita Hiburan Terhadap Perhatian Politik - Muhammad Abiyu Alzaky; Aliasan Aliasan; Jawasi Jawasi (ScidacPlus, 2025)
This study aims to determine the effect of entertainment news consumption on individual attention to political issues. The main focus of this study is to analyze the extent to which exposure to entertainment news can influence the level of public attention to political dynamics. This study was conducted in Air Batu Jaya Village, Talang Kelapa District, with 80 respondents. Data collection was carried out through questionnaires and documentation methods with a quantitative approach. Data analysis used a t-test to measure partial influence and a determination test (R²) to determine how much the independent variable contributed to the dependent variable. Based on the results of the research that has been conducted, it was found that entertainment news consumption (soft news) has a real and significant influence on the level of public attention to political issues.